Elevated platelet-to-lymphocyte ratio predicts poor clinical outcomes in non-muscle invasive bladder cancer: a systematic review and meta-analysis - Hu, Wenfeng; Liang, Jinze; Luo, Jin; Fan, Jie; Hu, Huaichun; Wang, Xinwen; Zhou, Peng; Zhang, Xiaoyi; Zhou, Jie (Frontiers in Immunology, 2025)
IntroductionThe prognostic significance of platelet-to-lymphocyte ratio (PLR) in non-muscle invasive bladder cancer (NMIBC) remains controversial despite numerous investigations. This study aimed to systematically evaluate the prognostic value of PLR in NMIBC.Materials and methodsAn extensive systematic search was executed utilizing four major electronic databases: Embase, PubMed, Web of Science, and Cochrane Library. The prognostic significance of PLR was assessed using pooled hazard ratios (HRs) with 95% CIs. Forest plots were used to present data visualization and statistical summaries, illustrating the effects of individual studies and the reliability of the pooled results. Funnel plot analysis and Egger’s test were employed to evaluate the potential presence of publication bias. Sensitivity analysis was performed to assess the robustness of the pooled findings. Subgroup analysis and meta-regression were used to identify sources of heterogeneity.ResultsEleven retrospective studies encomprising 3,566 patients met the inclusion criteria. Elevated PLR notably correlated with inferior progression-free survival (PFS) (HR=2.132, 95% CI: 1.146-3.967, p=0.017) and relapse-free survival (RFS) (HR=1.732, 95% CI: 1.174-2.554, p=0.006). No statistically meaningful correlation emerged in cancer-specific survival (CSS) (HR=1.218, 95% CI: 0.800-1.854, p=0.358) or overall survival (OS) (HR=1.350, 95% CI: 0.611-2.983, p=0.459). Publication bias was detected in RFS analyses (Egger’s test, P=0.010). Sensitivity analysis demonstrated that the pooled results were robust. Subgroup analysis and meta-regression identified geographic differences and patient characteristics as key sources of heterogeneity in RFS outcomes. Subgroup analysis indicated that geographic differences and sample size were potential sources of heterogeneity in PFS results.DiscussionThis study comprehensively analyzed 11 studies and 3,566 NMIBC cases and found that elevated PLR was significantly associated with poorer RFS and PFS, suggesting that PLR can be used as a prognostic biomarker for the management of NMIBC. The prognostic value of PLR may be related to immune regulation and inflammatory response in the tumor microenvironment; nevertheless, further studies are needed to elucidate its mechanism and establish its clinical application.ConclusionsThis study demonstrates that elevated PLR serves as an independent predictor of poor PFS and RFS in NMIBC patients. As a cost-effective biomarker, PLR shows promise in risk stratification and treatment planning. However, large-scale prospective studies are warranted to validate these findings and establish standardized cut-off values.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024621307, identifier CRD42024621307.